A homologous series of first-row transition-metal complexes of 2,2'-bipyridine and their ligand radical derivatives: trends in structure, magnetism, and bonding. - Irwin, M; Doyle, L; Krämer, T; Herchel, R; McGrady, J; Goicoechea, J (2012)
The organometallic first-row transition-metal complexes [M(2,2'-bipy)(mes)2] (M = Cr (1), Mn (2), Co (4), Ni (5); 2,2'-bipy = 2,2'-bipyridine; mes = 2,4,6-Me3C6H2) were reacted with potassium and a suitable alkali-metal sequestering agent to yield salts of the anionic species [M(2,2'-bipy)(mes)2](-). The neutral parent compounds and their corresponding anionic congeners were characterized by single-crystal X-ray diffraction in [Cr(2,2'-bipy)(mes)2]·1.5C6H6, [Mn(2,2'-bipy)(mes)2], [Co(2,2'-bipy)(mes)2]·THF, [Ni(2,2'-bipy)(mes)2], [K(dibenzo-18-crown-6)·THF][Cr(2,2'-bipy)(mes)2]·2THF, [K(18-crown-6)][Mn(2,2'-bipy)(mes)2]·2THF, [K(18-crown-6)][Mn(2,2'-bipy)(mes)2]·0.67py·0.67tol, [K(2,2,2-crypt)][Co(2,2'-bipy)(mes)2], and [K(2,2,2-crypt)][Ni(2,2'-bipy)(mes)2]. These species, along with the previously reported neutral and anionic iron complexes [Fe(2,2'-bipy)(mes)2](0/-) (3/3(-)), form a homologous series of compounds which allow for an in-depth study of the interactions between metals and ligands. Single-crystal X-ray diffraction data, DFT calculations, and various spectroscopic and magnetic measurements indicate that the anionic complexes (1(-)-5(-)) can be best formulated as M(II) complexes of the 2,2'-bipyridyl radical anion. These findings complement recent studies which indicate that bond metric data from single-crystal X-ray diffraction may be employed as an important diagnostic tool in determining the oxidation states of bipyridyl ligands in transition-metal complexes.